Eksplorasi Etnomatematika Bentuk Geometri Peninggalan Syekh Ahmad Muttamakkin - Intan Ayu Andriyani; Nur Diana Fitria; Eka Zuliana (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
Syekh Ahmad Muttamakkin was one of the great scholars of the archipelago in the 18th century and became a role model for the community in Kajen, Pati. The history of Syekh Ahmad Muttamakkin must be preserved so that it does not disappear over time. In this way, researchers link the history of Syekh Ahmad Muttamakkin's legacy with the material of mathematical geometry. In this case the researcher associates local culture with mathematical activity. This research uses descriptive qualitative research with an ethnographic approach. The object of this study is ethnomathematics on the legacy of Syekh Ahmad Muttamakkin which includes mosque buildings, ornaments, and objects left by Syekh Ahmad Muttamakkin. The data in this study were obtained from observations, interviews, documentation, and literature from journals and internet articles. The purpose of this study is to find out the ethnomathematics studies contained in the legacy of Syekh Ahmad Muttamakkin and to dig up philosophical information about these objects. The result of this study is that the researcher found a link between the mathematical concept of recognizing geometric shapes and the legacy of Syekh Ahmad Muttamakkin. In an ethnomathematics exploratory study, in terms of the shape of mosque buildings, ornaments, and relics of Syekh Ahmad Muttamakkin, it shows that there is a connection with mathematical material, namely regarding geometry and shapes.